TRADISI MAKAN PUNDUTAN DI DESA PULAU BETUNG 1970-2025 - Agung Nugroho; Deki Syaputra ZE (Universitas Batanghari Jambi, 2026)
The tradition of eating pundutan in Pulau Betung Village is a cultural heritage that has been carried out from generation to generation during customary and religious events (such as holidays, weddings, and circumcisions). The main purpose of this tradition is to strengthen social relations, share, and symbolize the harmony and unity of the community. Its implementation in Pulau Betung Village officially began around 1970 and is regulated by local customary law called